A cross-sectional observational study to assess the awareness regarding needle prick injuries among health care providers of a tertiary care teaching hospital in Madhya Pradesh, India - Guleri, Sunil K.; Panika, Ram K. (International Journal Of Community Medicine And Public Health, 2019)
Background: Health care workers (HCW) are at risk of an occupational exposure to blood borne diseases like HIV and Hepatitis B through accidental needle stick injuries. This study was conducted to assess the awareness regarding needle prick injuries among health care providers and their exposure to NSIs in a tertiary care medical college hospital with 750 bed capacity. Methods: This cross sectional observational study was conducted on 300 voluntarily participated HCWs out of total 650 HCWs. A semi structured questionnaire was used to assess their knowledge about exposure to blood and body fluids, needle stick injuries and associated risks and post exposure prophylaxis. Details of previous exposures to NSIs in last one year (2017-18) were also asked and their opinion about role and responsibilities of hospital administration for management of NSI was also recorded. Results: More than 90% HCWs were aware of exposure to blood and body fluids, 80.7% were aware of needle stick injuries, all 100% were aware of transmission of HIV and Hepatitis B from NSis and 78% were aware of post exposure prophylaxis. 97 cases of NSIs occurred in last one year which was higher than estimated EPInet data. Injection needle was most commonly (93.8%) involved in causing accidental NSIs. Conclusions: Practice of universal precautions and standard injection procedures by HCWs should be followed and education, training, and group insurance should be provided by hospital administration for prevention of NSIs.